Metabolomics Analysis of Hippocampus and Cortex in a Rat Model of Traumatic Brain Injury in the Subacute Phase - Zheng, Fei; Zhou, Yan-Tao; Li, Peng-Fei; Hu, En; Li, Teng; Tang, Tao; Luo, Jie-Kun; Zhang, Wei; Ding, Chang-Song; Wang, Yang (Frontiers in Neuroscience, 2020)
Traumatic brain injury (TBI) is a complex and serious disease as its multifaceted pathophysiological mechanisms remain vague. Molecular changes of hippocampal and cortical dysfunction in the process of TBI are poorly understood especially their chronic effects on metabolic profiles. Here, we utilize metabolomics based liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS) coupled with bioinformatics method to assess perturbation of brain metabolism in rat hippocampus and cortex on day 7. The results revealed a signature panel which consisted of 13 identified metabolites to facilitate targeted interventions for subacute TBI discrimination. Purine metabolism change in cortical tissue, taurine and hypotaurine metabolism in hippocampal tissue were detected. Furthermore, the associations between metabolite markers and perturbed pathways were analyzed based on databases: 64 enzyme and 1 pathway was evolved in TBI. The findings represented significant profiling changes, and provided unique metabolite-protein information in a rat model of TBI following subacute phase. This study may inspire scientists and doctors to further their studies, and provide potential therapy targets for clinical interventions.